Pregnancy planning and acceptance and maternal psychological distress during pregnancy: results from the National Perinatal Survey, France, 2016 - Caroline Moreau; Camille Bonnet; Maxime Beuzelin; Béatrice Blondel (BMC, 2022)
Abstract Background Studies report heightened risks of mental health problems among women who experience an unintended pregnancy, but few consider the complexity of pregnancy intentions. In this study, we evaluate how different dimensions of pregnancy intentions (pregnancy planning and pregnancy acceptance) relate to two maternal depressive symptoms and perceived psychological distress. Methods This study draws from a cross-sectional national survey conducted in all maternities in France over a one-week period in 2016. All mothers 18 years and older who had a live birth during the study period were invited to participate. After excluding women who underwent infertility treatment, our analytical sample included 10,339 women. We first described levels and correlates of pregnancy planning and acceptance, defined in four categories; planned/welcomed, unplanned/welcomed, planned/unwelcomed, unplanned/unwelcomed. We then assessed the bivariate and multivariate associations between pregnancy planning and acceptance and two outcomes: women's self-perceived psychological health and the presence of two depressive symptoms during pregnancy. We used multivariate logistic regressions to evaluate these associations, after adjusting for socio-demographic and medical factors. Results Altogether 7.5 to 24.1% of mothers perceived their psychological health during pregnancy was poor, according to pregnancy planning and acceptance categories and 10.3 to 22.4% indicated feelings of sadness and loss of interest during pregnancy, according to pregnancy planning and acceptance categories. As compared to women with planned/welcomed pregnancies, the odds of perceived poor psychological health and depressive symptoms were 2.55 times (CI 2.20-2.95) and 1.75 times higher (CI 1.51-2.02), respectively, among unplanned/unwelcomed pregnancies and 2.02 (CI 1.61-2.53) and 2.07 (CI 1.7-2.5) higher, among planned/unwelcomed pregnancies. Among women with unplanned pregnancies, we also found higher odds of perceived poor psychological health among women whose pregnancy was unwelcomed while the odds of depressive symptoms were not different by pregnancy planning status among women with unwelcomed pregnancies. Conclusions These findings consolidate previous reports of the association between pregnancy intentions and maternal psychological distress, while further specifying the relationship, which mostly depends on the acceptance of pregnancy timing rather than on pregnancy planning. Identifying women with low pregnancy acceptance can potentially enhance current medical practice by improving early detection of maternal depression.